Organochlorine pesticide residues in buffalo meat, liver, kidney, milk, and kariesh cheese - Mohamed, Asmaa S.M.; Saad, Mai F.; Wagih, Eman; Dawod, Yomna F.; Elzawahry, Radwa R. (Journal of Advanced Veterinary Research, 2024)
High-quality animal protein, vitamins B1, B6, and B12, as well as minerals like zinc, selenium, and iron, can all be found in buffalo meat and milk. Organochlorine pesticides (OCPs) have been widely utilized for many years because of their long duration of action, low cost, and toxicity against a variety of pests. Despite being outlawed everywhere, OCPs are still being used illegally. One of the main responsibilities of the food safety and public health sectors is to guarantee the safety and wholesomeness of such food products before they are made available to the public. In order to determine the residual OCP contents in retailed buffalo meat, liver, kidney, milk, and kariesh cheese, this study was conducted. The obtained results in the current investigation revealed the detection of OCPs at 75%, 40%, 25%, 60%, and 80% in the examined buffalo raw milk, kariesh cheese, meat, kidneys, and liver. Different OCPs were detected at variable concentrations; however, such concentrations were within the established permissible limits in Egypt. In conclusion, OCPs are still in use in Egyptian agricultural activities and residual concentrations can be detected in the meat, offal, and dairies. Therefore, it is highly advised to continuously check for OCP residues in foods with both animal and plant origins. Additionally, it is strongly advised that farmers become more aware of the negative consequences of OCPs.